An Analysis of Teachers’ Understanding of the Nature of the Indonesian Language and Literature Curriculum in Junior High Schools - Alwihiyatun Alwihiyatun; Dewi Sri Rahayu; Fazwa Alya Nisa (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine: junior high school teachers’ understanding of the fundamental concepts underlying the nature of the Indonesian Language and Literature curriculum; how teachers interpret the goals, scope, and components of the curriculum in their instructional practices; the factors that influence the level of teachers’ understanding of the curriculum’s nature; and the implications of teachers’ curriculum understanding for classroom instruction. This research employs a descriptive qualitative approach to naturally portray junior high school teachers’ understanding of the nature of the Indonesian Language and Literature curriculum. Primary data were obtained through interviews, observations, and reviews of teaching documents, while secondary data were drawn from curriculum documents, implementation guidelines, teaching modules, and relevant literature. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. This approach enables a comprehensive portrayal of how teachers understand and implement the curriculum in their instructional practices. The study shows that the descriptive qualitative approach is effective for providing an in-depth and natural depiction of teachers’ understanding of the nature of the Indonesian Language and Literature curriculum at the junior high school level. Through complementary primary and secondary data, the research offers an authentic illustration of how teachers interpret and apply curriculum components. The use of interviews, observations, and documentation yields comprehensive data, while the Miles and Huberman analysis ensures systematic, accurate, and meaningful findings.